2016
DOI: 10.1007/s13312-016-0876-2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and parathyroid response in critically-ill children: Association with illness severity and clinical outcomes

Abstract: Critically ill children have high prevalence of vitamin D deficiency. Parathyroid gland response secondary to hypocalcemia or vitamin D defiency is impaired in critical illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 20 publications
4
22
2
Order By: Relevance
“…Although several studies showed that critically ill children have vitamin D deficiency and its level is related to the severity of illness, but no study as yet is found that shows any improvement in the outcome of ill children after vitamin D supplementation similar to our study [4,6,13]. Walker SP and Golden MH in 1988 and later Richard SA et al in 2012 found that there is a lag in height gain before 85% of weight is achieved.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Although several studies showed that critically ill children have vitamin D deficiency and its level is related to the severity of illness, but no study as yet is found that shows any improvement in the outcome of ill children after vitamin D supplementation similar to our study [4,6,13]. Walker SP and Golden MH in 1988 and later Richard SA et al in 2012 found that there is a lag in height gain before 85% of weight is achieved.…”
Section: Resultssupporting
confidence: 76%
“…These randomized groups were enclosed in the opaque envelop, which were opened after enrollment of children in the study. The patients falling in study group were given High dose i.e., 6 Excluded with the WHO recommended protocol for facility based care of SAM and other group was only given of management of SAM [7]. Patients attendant were unaware of the group in which they were treated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance to us, Shah et al (26) found that there was no statistically significant difference as regard diagnosis of sepsis or septic shock on admission in patient with VDD. In contrast, Ponnarmeni et al (25) demonstrated that the prevalence of VDD among critically ill children with sepsis was 50.8%, which was significantly higher than in healthy controls (40.2%) and found that patients with VDD had an increased incidence of shock, although the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 75%
“…McNally et.al., in 326 critically ill children, found that vitamin D deficiency was associated with increased length of stay and increased severity of illness (4). In contrast, Shah et.al., in 154 critically ill children with high prevalence of vitamin D deficiency, found no difference in mortality, length of stay, or severity of illness, but a decrease in acute respiratory distress syndrome in children with severe vitamin D deficiency when compared with critically ill children who were not deficient (5). Before making general recommendations, a meta-analysis or large epidemiological study examining the association between vitamin D deficiency status and pediatric outcomes is needed.…”
mentioning
confidence: 96%